Using Game of Thrones to Teach International Relations. Issue 3 (3rd July 2018) - Young, Laura D.; Carranza Ko, Ñusta; Perrin, Michael
ABSTRACT: Despite the known benefits of long-term, game-based simulations they remain underutilized in Political Science classrooms. Simulations used are typically designed to reinforce a concept and are short-lived, lasting one or two class sessions; rarely are entire courses designed around a single simulation. Creating real-world conditions in which students operate often requires the development of distinct cultures and shared experiences that only long-term interactions can generate. These long-term interactions create a community where the past interactions of players matter when making decisions about future action. Long-term role-playing also gives students a forum to fully immerse themselves in the material resulting in deeper content comprehension. This article presents a framework for using a long-term, game-based simulation based on the popular television show Game of Thrones. The simulation uses an active learning approach to help students understand a variety of topics related to International Relations and related fields. The article concludes with a discussion on how the simulation can be modified to fit a variety of non-Political Science courses as well as provides the framework for an experimental design to test the effectiveness of the simulation.